The oscillations of the dynamical systems with hysteresis characteristics excited stochastic parameter and forces. II - Menh, Nguyen Cao (Vietnam Journal of Mechanics, 1980)
In this paper, the problem in [1] is continued studying. The some special cases of the general problem are considered. The beam with internal friction under stochastic forces is analyzed. In this example the influence of the hysteresis character in material and the parameter in the system on the oscillations of the beam are shown.